Human oscillatory potentials: components of rod origin - Janáky, M; Goupland, S G; Benedek, G (Ophthalmologica (Basel), 1996)
Oscillatory potentials (OPs) evoked by white flashing light after dark or light adaptation (WDA and WLA conditions) and those evoked by blue flashing light stimulation against a dark background (BDA condition) were recorded in 16 healthy volunteers. When blue flashing light was employed over a scotopic background, the two major OPs of this response (OP2 and OP3) appeared with a latency time that sharply coincided with the third (OP3) and fourth (OP4) components of the OPs evoked by white flashes. The results provide evidence in support of the notion that various elements of OPs represent the activities of different retinal mechanisms, of which OP3 and OP4 seem to be of rod origin.